2019
DOI: 10.1111/jcmm.14397
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of ABCA3 lipid transport function by ivacaftor and genistein

Abstract: ABCA3 is a phospholipid transporter implicated in pulmonary surfactant homoeostasis and localized at the limiting membrane of lamellar bodies, the storage compartment for surfactant in alveolar type II cells. Mutations in ABCA3 display a common genetic cause for diseases caused by surfactant deficiency like respiratory distress in neonates and interstitial lung disease in children and adults, for which currently no causal therapy exists. In this study, we investigated the effects of ivacaftor and genistein, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 54 publications
(126 reference statements)
0
30
0
Order By: Relevance
“…Recently, Kinting et al (2019) demonstrated increased lipid transport activity as measured by the increased portion of labeled phosphatidylcholine (TopF‐PC) filled vesicles and increased fluorescence intensity of filled vesicles when A549 cells expressing the type II mutant c.1702A>G;p.N568D were exposed to CFTR potentiators ivacaftor and genistein. While not all ABCA3 type II mutants studied demonstrated increased lipid transport activity in response to ivacaftor or genistein, these data demonstrate proof of concept for development of pharmacologic strategies to correct ABCA3 function among symptomatic infants and children (Kinting et al, 2019). Quantitative differences in mean vesicle diameter and immunoflourescent colocalization may be useful in pathogenicity screening of uncharacterized ABCA3 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kinting et al (2019) demonstrated increased lipid transport activity as measured by the increased portion of labeled phosphatidylcholine (TopF‐PC) filled vesicles and increased fluorescence intensity of filled vesicles when A549 cells expressing the type II mutant c.1702A>G;p.N568D were exposed to CFTR potentiators ivacaftor and genistein. While not all ABCA3 type II mutants studied demonstrated increased lipid transport activity in response to ivacaftor or genistein, these data demonstrate proof of concept for development of pharmacologic strategies to correct ABCA3 function among symptomatic infants and children (Kinting et al, 2019). Quantitative differences in mean vesicle diameter and immunoflourescent colocalization may be useful in pathogenicity screening of uncharacterized ABCA3 variants.…”
Section: Discussionmentioning
confidence: 99%
“…We also recommend that further clinical trial should assess the effect of drugs potentiating the effect of ABCA3 like the cystic fibrosis transmembrane conductance regulator e.g. ivacaftor and genistein [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to successful CFTR therapy, the potentiators ivacaftor and genistein may rescue protein functionality. Recently, these potentiators were shown to rescue the ABCA3 phospholipid transport function of three different mutations stably expressed in A549 cells [145].…”
Section: Therapymentioning
confidence: 99%